Reeks met haakjes
\(3(-4x+2)=2-(11+x)\)
\(\begin{align} & \color{red}{3} (-4x+2)& = & 2 \color{red}{-} (11+x) \\\Leftrightarrow & -12x+6& = &2-11-x \\\Leftrightarrow & -12x \color{red}{+6} & = &-9 \color{red}{-x} \\\Leftrightarrow & -12x \color{red}{+6} \color{blue}{-6} \color{blue}{+x} & = &-9 \color{red}{-x} \color{blue}{+x} \color{blue}{-6} \\\Leftrightarrow & -12x+x& = &-9-6 \\\Leftrightarrow & -11x& = &-15 \\\Leftrightarrow & \frac{-11x}{ \color{red}{-11} }& = &\frac{-15}{ \color{red}{-11} } \\\Leftrightarrow & x = \frac{15}{11} & & \\ & V = \left\{ \frac{15}{11} \right\} & \\\end{align}\)